Common Fixed Points for Nonlinear Quasi-Contractions of Ćirić Type - Fei He (Abstract and Applied Analysis)
We establish common fixed points theorems for two self-mappings satisfying a nonlinear contractive condition of Ćirić type with a Q-function. Furthermore, using the scalarization method, we deduce some results of common fixed point in tvs-cone metric spaces with a c-distance. As application, we give a positive answer to the question of Ćirić et al. posed in 2012. Our results extend and generalize many recent results.